2019
DOI: 10.13057/biodiv/d201219
|View full text |Cite
|
Sign up to set email alerts
|

The diversity of useful plants and botanical knowledge of the Rejang Tribe in Kepahiang District, Bengkulu Province, Indonesia

Abstract: Abstract. Wiryono, Sriwahyuni, Winanda GA, Saprinurdin, Nurliana S. 2019. The diversity of useful plants and botanical knowledge of the Rejang Tribe in Kepahiang District, Bengkulu Province, Indonesia. Biodiversitas 20: 3599-3607. The rural people derive multiple benefits from the highly diverse plants in their traditional gardens and the nearby natural forests. However, the conversion of natural forests and traditional gardens into monoculture plantations in many areas has reduced the plant diversity, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
(59 reference statements)
1
3
0
Order By: Relevance
“…Moreover, it was evident that the young generation is less involved in traditional healing enterprises in the region, possibly because parents are not transferring the indigenous knowledge to the young generation, youths are disinterested in the sector, or youths are encouraged to pursue formal or modern healing industry, which is financially worthwhile. Similarly, the decline of traditional healing knowledge among young generations has been reported in other ethnobotanical studies in Brazil (Miguéis et al 2019), Nigeria (Olanipekun 2023) and Indonesia (Wiryono et al 2019).…”
Section: Resultssupporting
confidence: 65%
“…Moreover, it was evident that the young generation is less involved in traditional healing enterprises in the region, possibly because parents are not transferring the indigenous knowledge to the young generation, youths are disinterested in the sector, or youths are encouraged to pursue formal or modern healing industry, which is financially worthwhile. Similarly, the decline of traditional healing knowledge among young generations has been reported in other ethnobotanical studies in Brazil (Miguéis et al 2019), Nigeria (Olanipekun 2023) and Indonesia (Wiryono et al 2019).…”
Section: Resultssupporting
confidence: 65%
“…As a result, this knowledge is not well documented and can be lost. For example, the loss of traditional knowledge of local plants have been reported from the studies in Nigeria (Ayantunde et al 2008), Dominica (Quinlan and Quinlan 2007), Mexico (Saynes-Vaquez et al 2016), Brazil (Sousa et al 2012, and in Bengkulu, Indonesia (Wiryono et al 2017(Wiryono et al , 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in rural communities near Chapada Diamantina National Park in Bahia, Brasil, women also knew more medicinal plants than men (Voeks 2007). In Rejang Tribe, in Bengkulu, Indonesia, women significantly new plant names and uses than men (Wiryono et al 2019a). However, some studies reported the opposite result, i.e., men knew more botanical knowledge than women.…”
Section: Relationship Between Medicinal Plant Knowledge and Age Gende...mentioning
confidence: 99%